MISSING THE MARK: THE IMPORTANCE OF FINANCIAL ANXIETY IN FINANCIAL SKILLS TRAINING FOR FOSTER YOUTH - Keller, Amanda (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2023)
It is well established that many former Canadian foster youth struggle with financial issues after aging out of care. Much of the financially focused intervention literature speaks to financial literacy training within independent living programming (ILP) or financial empowerment within individual development accounts (IDAs). These important programs offer educational modules to address financial skills or increase youth access to savings. Yet they are not sufficient, as neither addresses the emotional side of personal financial decision-making. Growing up in poverty can create emotional challenges related to money, such as financial anxiety. Financial anxiety affects quality of life in complex ways. Using three clinical composite profiles of youth aging out of the youth protection system in Quebec, this paper highlights some of the complex challenges faced by foster care alumni in dealing with economic insecurities. It is our proposition that we must be more mindful of current and former foster youth’s financial well-being and adapt financial literacy training accordingly. Further, these programs must be assessed for short- and long-term efficacy. Neglecting to measure and address financial anxiety for foster youth and alumni of care risks setting them up for preventable hardships and failures. This paper thus proposes that Canadian child welfare organizations and research teams must further develop this area of inquiry and intervention.